2014
DOI: 10.1111/bjd.13359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on response to systemic treatment in patients with psoriasis: a retrospective case-control study

Abstract: In our retrospectively studied cohort, smoking did not affect response to systemic treatment in patients with psoriasis. A prospective study examining the complex relationship between smoking, psoriasis and response to systemic therapy is warranted to explore this association better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
2
16
1
Order By: Relevance
“…The data from the cohort of patients with psoriasis for Germany and Switzerland analysed prospectively in this study confirms the results of previous prospective (35)(36)(37) and retrospective (38)(39)(40) studies, in demonstrating that active smoking does not significantly affect the treatment response of skin lesions in psoriasis to systemic therapies. Menter et al reported the absence of a correlation between active tobacco use and PASI 75 response in a prospective study with 814 patients treated with adalimumab (35).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The data from the cohort of patients with psoriasis for Germany and Switzerland analysed prospectively in this study confirms the results of previous prospective (35)(36)(37) and retrospective (38)(39)(40) studies, in demonstrating that active smoking does not significantly affect the treatment response of skin lesions in psoriasis to systemic therapies. Menter et al reported the absence of a correlation between active tobacco use and PASI 75 response in a prospective study with 814 patients treated with adalimumab (35).…”
Section: Discussionsupporting
confidence: 86%
“…No difference between smoking status and efficacy of TNF-α blockers and ustekinumab was, however, found in a retrospective Italian study of 350 patients (39). A smaller retrospective study yielded similar results; however, only 36 non-smokers and 20 smokers met the inclusion criteria (38).…”
Section: Discussionmentioning
confidence: 83%
“…In this issue of the BJD , Kinahan et al . have investigated the effect of smoking on the response to systemic antipsoriatic treatment in a retrospective case–control study.…”
Section: Funding Sourcesmentioning
confidence: 99%
“…Based on the results obtained in the study by Kinahan et al ., it would be of value to perform a prospective study, with a preliminary sample size calculation and primary outcome measures, including more than one measure of disease severity, data on all potential confounders and possibly also patient‐reported outcome measures. The goal of this study would be to determine the influence of smoking on the response to specific systemic treatments, adjusting for known risk factors involved in psoriasis and to investigate whether there is a dose–response relationship with the degree of smoking and response to systemic treatment.…”
Section: Funding Sourcesmentioning
confidence: 99%
“…5 to 10% of body weight) increases the responsiveness of obese patients to any systemic treatments [62][63][64]. Smoking habit has been associated to onset and worsening of psoriasis, and smoking cessation can positively affect the disease course [65]. Patients with psoriasis exhibit a decreased level of physical activity, possibly for both psychological and physiological reasons [66].…”
Section: Management Of Patients With Moderate To Severe Psoriasis Andmentioning
confidence: 99%